Assessment of pulmonary arteriovenous malformation with ultra-short echo time magnetic resonance imaging. Issue 147 (February 2022) - Hamamoto, Kohei; Chiba, Emiko; Oyama-Manabe, Noriko; Yuzawa, Hironao; Shinmoto, Hiroshi
Highlights: Diagnosing and treating pulmonary arteriovenous malformations (PAVM) are important. CT is generally used in assessing PAVMs; however, radiation burden is a major drawback. Ultra-shot TE (UTE) MRI could detect small PAVMs comparable to CT. The measurements of PAVM size were highly correlated between CT and UTE MRI. UTE MRI is useful for PAVM assessment without radiation exposure or contrast media. Abstract: Purpose: The purpose of this study was to evaluate the diagnostic performance of ultra-short echo time magnetic resonance imaging (UTE MRI) in the assessment of pulmonary arteriovenous malformation (PAVM). Methods: Eighteen consecutive patients (mean [± standard deviation] age, 48.6 ± 16.8 years) with 46 untreated PAVMs who underwent and thin-section computed tomography (CT) and UTE MRI with a 1.5-Tesla and 3-Tesla unit were retrospectively assessed. Two radiologists evaluated the diagnostic capabilities of UTE MRI for the detection and classification of PAVMs with reference to CT. Sensitivity, specificity, and kappa statistics were calculated with reference to CT. We also compared the differences in PAVM measurements between CT and MRI. Results: The sensitivity and specificity of UTE-MRI for the detection of PAVMs were 89.1% and 100%, respectively, for reader 1 and 87.0% and 100%, respectively, for reader 2. In the classification of PAVMs, inter-modality agreement in reader 1 and 2 were both substantial (κ = 0.78 and 0.69, respectively). The measurements of the PAVM feeding artery and sac on CT and MRI were strongly correlated in both readers 1 and 2 (R 2 = 0.981 and 0.983, respectively). Both readers 1 and 2 slightly underestimated the diameter of the PAVM feeding artery and sac on UTE MRI ( p < 0.001). Conclusion: This study indicates that UTE MRI is a feasible and promising modality for noninvasive assessment of PAVMs.